Synthesis of optimal non-linear systems of stochastic stabilization - Блохин, Л. Н. (Proceedings of National Aviation University (archive), 1998)
Here we propose a new approach to synthesis of high-precision systems of stochastic stabilization of an object with arbitrary dynamics including considerable non-linear members. The procedure of synthesis presupposes using the results of structural identification received according to the proposed algorithm of required models of dynamics of non-linear member in the process of its simulation on computers at certain stochastic input signals. The results of the synthesis make possible to explain some effects, emergence of which is possible in the created system